The sounds of silence: music in the Heroic Age of Antarctic exploration - Philpott, CJ (The Polar Journal, 2013)
The leaders of the Antarctic expeditions of the Heroic Age (c.18971922)commonly encouraged their men to engage in cultural activities in order to keepthem occupied, alleviate boredom, strengthen the sense of camaraderie and wardoff symptoms of depression. While the importance of literary activities (such asjournal keeping and newspaper production) to various Heroic Age expeditionshas been acknowledged in the literature, little research has yet to be conductedinto the vast quantity and variety of music that was taken to and/or created inAntarctica during the same period, despite the significant role that it appears to have played in the everyday lives of the men who ventured there. Drawing onthe written journals and published accounts of the expeditions, musical scoresand expeditionary newspapers, this article explores the role and value of musicin the Antarctic expeditions of the Heroic Age and examines some of the earliestknown musical responses to Antarctica, including the first Antarctic opera,various original sledging songs, and the unique collection of occasional songscomposed aboard the Morning in 1902 by Gerald S. Doorly. Collectively, thismusic not only provides a record of the explorers experiences and perceptionsof the Antarctic significantly, it also offers valuable insight into exactly what they did to entertain themselves and boost team morale during long voyages at sea, gruelling sledge journeys and freezing cold, lonely winters in Antarctica.